Efficient OWL Reasoning with Logic Programs - Evaluations. - Rudolph, S; Krötzsch, M; Hitzler, P; Sintek, M; Vrandecic, D (Springer, 2007)
We report on efficiency evaluations concerning two different approaches to using logic programming for OWL [1] reasoning and show, how the two approaches can be combined. © Springer-Verlag Berlin Heidelberg 2007.